Appleton & Lange's review of internal medicine - Goldlist, Barry J. (Appleton & Lange, 1996)
A comprehensive review of the major issues in internal medicine, designed to prepare medical students for success on the USMLE Step 2. The Third Edition contains over 1,000 exam-type questions, answers with detailed explanations, and a practice test for self-assessment.